Physicochemical and toxicological characterization of hazardous wastes from an old glasswork dump at southeastern part of Sweden. (December 2019) - Jani, Yahya; Burlakovs, Juris; Augustsson, Anna; Marques, Marcia; Hogland, William
Abstract: More than 34 old glasswork sites in the southeastern part of Sweden pose a permanent threat to human and environmental health due to the presence of toxic trace elements in open dumps with glass waste. The possibility of leaching of trace elements from different fractions of the disposed waste needed to be assessed. In the present investigation, leachate from a mixture of soil and waste glass of particle sizes of less than 2 mm (given the name fine fraction) was characterized by analyzing the pH (7.3), total organic content (TOC < 2%), organic matter content (4.4%), moisture content (9.7%), chemical oxygen demand (COD, 163 mg/kg) and trace elements content, being the values in accordance to the Swedish guidelines for landfilling of inert materials. However, very high trace elements content was found in the fine fraction as well as in all colors of waste glass, whose values were compatible to hazardous waste landfill class. Tests with Lepidium sativum growing in the fine fraction as substrate revealed chronic toxicity expressed as inhibition of root biomass growth in 11 out of 15 samples. Additionally, leachate from fine fractions posed acute toxicity to genetically modified E. coli (Toxi-Chromotest). This study highlights the importance of combining physicochemical characterization with toxicity tests for both solid waste and leachate obtained from different waste fractions for proper hazardousness assessment supporting decision making on remediation demands. Highlights: Physicochemical properties and toxicity combined for waste glass characterization. Risk assessment of dumped waste glass must address solid and leachate properties. Old glassworks dumps represent hazards potential for human and environmental health.